96.1k views
2 votes
Y - 58 = -43

Helppppp

Y - 58 = -43 Helppppp-example-1

2 Answers

2 votes

Answer:

y = 15

Explanation:

y - 58 = -43

add 58 to both sides

y = 15

User Riyas Ac
by
5.2k points
0 votes

Answer:

y = 15

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

y - 58 = -43

Step 2: Solve for y

  1. Add 58 on both sides: y = 15

Step 3: Check

Plug in y into the original equation to verify it's a solution.

  1. Substitute in y: 15 - 58 = -43
  2. Subtract: -43 = -43

Here we see that -43 does indeed equal -43.

∴ y = 15 is the solution to the equation.

User Idris Mokhtarzada
by
4.7k points